Anatomizing Social Media Content on Covid-19 in Pakistan - Dr. Farasat Rasool; Arif Ahmed; Zaighum, Zeeshan (Journal of Peace, Development and Communication, 2022)
The coronavirus pandemic also name as (COVID-19) was first identified in Wuhan, Hubei China. From where it spread to more than 177 countries causing a huge number of deaths. Although social media played a crucial role in spreading information about the pandemic, however, on the other side social media is blamed for reporting many fake news and rumors which lead to further spread of the pandemic. The objectives of this research are to investigate the role of social media after the outbreak of COVID 19 in Pakistan. This study will also highlight the spread of misinformation and rumors about the existence and treatments of COVID 19 on social media that lead to deaths and the spread of the pandemic. The researchers selected the top two platforms of social media namely Facebook and YouTube for the collection of data. The researcher analyzed the social media content for one year from 15 March 2020 to 15 March 2021 and reported the results. The results highlight that social media played a significant role in creating awareness among the people of Pakistan. However, due to the lack of censorship, the majority of available information on social media regarding the coronavirus is fake and misleading. Which may lead to further deaths and the spread of the Pandemic in Pakistan. The researchers concluded that the frequency of misinformation is higher than actual information. Social media should be used with care and responsibility to control the spread of the pandemic in Pakistan.